2003
DOI: 10.1212/01.wnl.0000094326.30791.2d
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diabetes and hyperglycemia on clinical course after intracerebral hemorrhage

Abstract: Both diabetes and admission hyperglycemia in nondiabetic patients are predictors of poor outcome after supratentorial ICH. This may be related to the greater incidence of cerebral and infectious complications in diabetic patients and of cerebral complications in hyperglycemic nondiabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
1
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 24 publications
5
122
1
7
Order By: Relevance
“…A large number of observational studies (21 studies, total number of patients=12 145, Table S6)2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32 have examined the association between glucose with ICH outcome with the majority (15 studies, total n=11 161) defining hyperglycemia on the basis of single glucose measurement. One notable study was the post hoc analysis of the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT) II study (n=2653) 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of observational studies (21 studies, total number of patients=12 145, Table S6)2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32 have examined the association between glucose with ICH outcome with the majority (15 studies, total n=11 161) defining hyperglycemia on the basis of single glucose measurement. One notable study was the post hoc analysis of the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT) II study (n=2653) 30.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation was based on association of hyperglycemia and poor outcome in observational studies 2, 3, 4, 5. The major limitation of these studies is use of single glucose measurement not accounting for potential glucose fluctuations after ICH.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies indicate that hyperglycaemia may increase brain oedema [12], inflammatory reaction [13], free radical injury [14] and excitotoxic or apoptotic cell death after stroke [15], but these results have not yet been demonstrated in humans to our knowledge. Although several studies have described possible effects of hyperglycaemia in ICH patients [4,5,[16][17][18][19][20][21], these studies used either small populations [5,16,17,19] or long enrolment periods [4]. Two small prospective studies [17,22] showed that hyperglycaemia is independently associated with shortterm mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have addressed this topic with regard to haemorrhagic stroke and no consensus has been established on the associated risks. A prospective study conducted in a single Italian centre indicated that hyperglycaemia is an independent predictor of 3 day and 3 month mortality in non-diabetic, non-comatose patients after supratentorial intracerebral haemorrhage (ICH) [4]. In contrast, a population-based retrospective study conducted in Finland suggested that high admission blood glucose is the result of serious ICH [5].…”
Section: Introductionmentioning
confidence: 99%
“…This independently predicts higher mortality rates in patients with and without diabetes [86,87]. In addition, hyperglycemia is associated with larger hematoma volumes and more intraventricular hemorrhage (IVH) [86,87].…”
Section: Supportive Carementioning
confidence: 99%